Wader ringing by the Wildfowl Trust, 1959-64 - Ogilvie, M A (Wildfowl, 1965)
In August 1959, the Wildfowl Trust’s rocket-netting equipment was successfully used to catch waders on the south shore of the Wash. The initiative for this operation came from Dr. C. D. T. Minton and other ringers under the collective name of the Wash Wader Ringing Group. Although the rocket-nets were designed for catching geese and had, apart from occasional sorties after ducks, been used exclusively for this purpose, the equipment required no modification in kind for wader-netting. The greatest single obstacle to catching waders with nets thrown over them, as opposed to flight-netting, is finding suitably hard ground, frequented by the birds and preferably not ever covered by the tide, on which to place the nets. The topography of the Wash with its areas of salting and mud in front of the sea-wall and large fields behind provided the answer. During normal high tides the waders are driven off the mud-flats, over which they feed, on to the saltings. Here they roost until the water has receded. During periods of spring tides, however, the saltings are generally completely covered and the birds then fly over the sea-wall and roost in large, compact flocks on suitable fields, usually choosing ploughed land or fields with very short vegetation. It was this habit that was first observed and then taken advantage of by the Wash Wader Ringing Group using the rocket-nets. The catching was all done in daylight, the tides sometimes giving us two chances in a day, more often just one.